Detection of Osseous Metastasis by 18F-NaF/18F-FDG PET/CT Versus CT Alone. (March 2015) - Sampath, Srinath C.; Sampath, Srihari C.; Mosci, Camila; Lutz, Amelie M.; Willmann, Juergen K.; Mittra, Erik S.; Gambhir, Sanjiv S.; Iagaru, Andrei
Abstract : Purpose: Sodium fluoride PET ( 18 F-NaF) has recently reemerged as a valuable method for detection of osseous metastasis, with recent work highlighting the potential of coadministered 18 F-NaF and 18 F-FDG PET/CT in a single combined imaging examination. We further examined the potential of such combined examinations by comparing dual tracer 18 F-NaF/ 18 F-FDG PET/CT with CT alone for detection of osseous metastasis. Patients and Methods: Seventy-five participants with biopsy-proven malignancy were consecutively enrolled from a single center and underwent combined 18 F-NaF/ 18 F-FDG PET/CT and diagnostic CT scans. PET/CT as well as CT only images were reviewed in blinded fashion and compared with the results of clinical, imaging, or histological follow-up as a truth standard. Results: Sensitivity of the combined 18 F-NaF/ 18 F-FDG PET/CT was higher than that of CT alone (97.4% vs 66.7%). CT and 18 F-NaF/ 18 F-FDG PET/CT were concordant in 73% of studies. Of 20 discordant cases, 18 F-NaF/ 18 F-FDG PET/CT was correct in 19 (95%). Three cases were interpreted concordantly but incorrectly, and all 3 were false positives. A single case of osseous metastasis was detected by CT alone, but not by 18 F-NaF/ 18 F-FDG PET/CT. Conclusions: Combined 18 F-NaF/ 18 F-FDG PET/CT outperforms CT alone and is highly sensitive and specific for detection of osseous metastases. The concordantly interpreted false-positive cases demonstrate the difficulty of distinguishing degenerative from malignant disease, whereas the single case of metastasis seen on CT but not PET highlights the need for careful review of CT images in multimodality studies.